(untitled) (Albayan Scientific Journal, 2023)
This research deals with the study of organic matter formed in forestlands (Podzol) and its importance as a natural resource in the development of agricultural lands. This study was conducted within the environmental range of soil, which included the organic horizon of two models of forest soils (podzol). One of them was formed under the vegetation cover of mixed natural forests, and the other formed under the vegetation cover of pine forests. The results of this study showed the extent of development in the organic horizon resulting from the accumulation of plant residues through the thickness formed on this horizon above the surface of mineral soil, and the layers forming the organic horizon in both sectors could be distinguished. In both soils, the results of the laboratory analyzes also showed a large discrepancy between the two types of soils formed under the vegetation of natural and coniferous forests.